2006
DOI: 10.1088/0960-1317/17/2/005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of frequency tuning using focused ion beam platinum deposition

Abstract: This paper presents and characterizes focused ion beam (FIB) platinum (Pt) deposition as a novel frequency tuning method for micromechanical resonators. FIB Pt deposited tuning was performed at room temperature and in contrast to other reported methods, frequency changes were achieved without any device failure. To perform the tuning, Pt was deposited on a 13 µm× 5 µm surface area at the free end of 3C silicon carbide (SiC) and polysilicon cantilever resonators in thicknesses ranging from 0.5 µm to 2.6 µm. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 38 publications
(50 reference statements)
1
36
0
Order By: Relevance
“…Q of all 4H-SiC cantilevers was nearly 200,000, while Q of the 3C-SiC cantilevers was nearly 20,000. Enderling et al reported Q of a 3C-SiC cantilever in vacuum condition to be 14,755 [16], and Q of our 3C-SiC cantilevers was similar to this reported value. Q of 4H-SiC cantilevers was 10 times that of 3C-SiC.…”
supporting
confidence: 89%
“…Q of all 4H-SiC cantilevers was nearly 200,000, while Q of the 3C-SiC cantilevers was nearly 20,000. Enderling et al reported Q of a 3C-SiC cantilever in vacuum condition to be 14,755 [16], and Q of our 3C-SiC cantilevers was similar to this reported value. Q of 4H-SiC cantilevers was 10 times that of 3C-SiC.…”
supporting
confidence: 89%
“…Silicon-based MEMS resonators are used as timing references in applications that require a device technology that can range from very low to ultra-high frequencies. Silicon carbide (SiC) is a promising material for RF MEMS because it has a high Young's modulus-to-density ratio, resulting in an acoustic velocity that is significantly above that of Si [3, 4]. Furthermore, SiC is more resistant to mechanical wear, more electrically stable at higher temperatures, and significantly more inert to environmental conditions than Si, making it a potential substitute for Si in harsh environment applications [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although differs by ~27 V between the two states, the gate-dependence of each mode relative to doesn't change, as seen in Figure 1d-e. Thus, apart from the shift, the phototuning process does not appear to alter the mechanical characteristics of the device in a significant way, unlike most passive tuning methods 25,26 . The individual resonance curves corresponding to the erased and = 30 states are shown in Figure 1f.…”
Section: Figure 1: (A)mentioning
confidence: 98%